Perspectives for electromagnetic radiation protection with MXenes. (February 2023) - Han, Meikang; Gogotsi, Yury
Abstract: The rapid development of communication and electronic technologies has brought forward new and compelling demands for electromagnetic radiation protection. Two-dimensional transition metal carbides and nitrides known as MXenes entered the field in 2016 and have been quickly reshaping it. Here, we provide a perspective on recent progress and challenges of the MXene family for protection against electromagnetic jamming, including electromagnetic interference (EMI) shielding and microwave absorption. We examine the intrinsic electronic and dielectric properties of MXenes, which are of critical importance for fundamental understanding of electromagnetic response. By tracing the state-of-the-art design strategies, we explore how to optimize MXene-based EMI shielding and microwave absorption materials. Particularly, we highlight the metrics and fundamental mechanisms of electromagnetic protection, aimed to clarifying common misconceptions, and objectively assess the performance of the reported materials. Finally, we discuss challenges to be addressed and give an outlook to future opportunities in the development of MXenes for electromagnetic radiation protection. Graphical abstract: Image 1